2017
DOI: 10.1016/j.vetmic.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

A spike-specific whole-porcine antibody isolated from a porcine B cell that neutralizes both genogroup 1 and 2 PEDV strains

Abstract: Porcine epidemic diarrhea (PED), caused by an alpha coronavirus, is a highly contagious disease and causes high morbidity and mortality in suckling piglets. Isolating PEDV neutralizing antibodies from porcine B cells is critical to elucidate the development of PEDV neutralizing antibodies and the protective mechanism of PEDV infection. Here, we described the isolation of a PEDV-neutralizing antibody from the B cell of a vaccinated pig. The antibody, named PC10, was demonstrated to target the conformational epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The S proteins of the highly virulent variants of PEDV have multiple amino acid insertions, deletions, and substitutions relative to the classic PEDV strains (e.g., CV777) (20). Since S protein is critically involved in PEDV entry, assembly, and induction of neutralizing antibodies (30,33,38,40,(54)(55)(56), the mutations likely have an influence on the virulence of PEDV. This idea is partly supported by recent studies of PEDV S protein large deletion mutants that were isolated from either cell culture (strain TC-PC177; cell adapted) (57) or swine farms (strain TTR-2) (58).…”
Section: Importancementioning
confidence: 99%
“…The S proteins of the highly virulent variants of PEDV have multiple amino acid insertions, deletions, and substitutions relative to the classic PEDV strains (e.g., CV777) (20). Since S protein is critically involved in PEDV entry, assembly, and induction of neutralizing antibodies (30,33,38,40,(54)(55)(56), the mutations likely have an influence on the virulence of PEDV. This idea is partly supported by recent studies of PEDV S protein large deletion mutants that were isolated from either cell culture (strain TC-PC177; cell adapted) (57) or swine farms (strain TTR-2) (58).…”
Section: Importancementioning
confidence: 99%
“…Additionally, for other nAbs, infection can be blocked through inhibiting critical intracellular processes, for example rotavirus transcription [17], nuclear translocation of human papilloma virus DNA [18], adenoviral uncoating [19], or measles virus assembly [20]. Several studies demonstrated that spike mAb can neutralize PEDV [21][22][23][24][25][26]. These studies mainly focused on locating the neutralizing domains of PEDV S protein, however, the mechanisms by which spike nAb neutralize the virus have not been defined completely.…”
Section: Introductionmentioning
confidence: 99%
“…The neutralization activity of the mAbs HK24 and HK44 against CSFV was tested via an immunofluorescence assay as described previously (54). Briefly, PK-15 cells were grown to 30-40% confluence in complete DMEM containing 10% FBS on 96-well plates at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%